The National Police Research Platform, Phase 2 (United States), 2013-2015 - Rosenbaum, Dennis P. ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.The purpose of the study was to implement a "platform-based" methodology for collecting data about police organizations and the communities they serve with the goals of generating in-depth standardized information about police organizations, personnel and practices and to help move policing in the direction of evidence-based "learning-organizations" by providing judicious feedback to police agencies and policy makers. The research team conducted three web-based Law Enforcement Organizations (LEO) surveys of sworn and civilian law enforcement employees (LEO Survey A Data, n=22,765; LEO Survey B Data, n=15,825; and LEO Survey C Data, n=16,483). The sample was drawn from the 2007 Law Enforcement Management and Administrative Statistics (LEMAS) database. Agencies with 100 to 3,000 sworn police personnel were eligible for participation. To collect data for the Police-Community Interaction (PCI) survey (PCI Data, n=16,659), each week department employees extracted names and addresses of persons who had recent contact with a police officer because of a reported crime incident, traffic accident or traffic stop. Typically, the surveys were completed within two to four weeks of the encounter.